Troublesome Tinnitus in Children: Epidemiology, Audiological Profile, and Preliminary Results of Treatment - G. Bartnik; A. Stepien; D. Raj-Koziak; A. Fabijanska; I. Niedzialek; H. Skarzynski (International Journal of Pediatrics)
Introduction. Although tinnitus often has a significant impact on individual's life, there are still few reports relating to tinnitus in children. In our tinnitus clinic, children with distressing tinnitus constitute about 0,5% of all our patients. Objectives. The aim of this study was to analyse children with troublesome tinnitus as regards epidemiology, audiological profile, and preliminary effects of the therapy. Methods. A retrospective study was carried out involving the cases of 143 children consulted in our Tinnitus Clinic in 2009. The selected group with troublesome tinnitus was evaluated and classified for proper category of Tinnitus Retraining Therapy (TRT). Results. The study showed that 41.3% of the children suffered from bothersome tinnitus. In this group 44.1% of the patients demonstrated normal hearing. The success of the therapy after 6 months was estimated on 81.4% of significant improvement. Conclusions. It is recommended that a questionnaire include an inquiry about the presence of tinnitus during hearing screening tests.